Sleep quality and cardiovascular response to physical/mental stress of policemen with and without stress. - Ceolin Nascimento, Reginaldo; Oliveira da Silva, Gustavo; Fortes-Queiroz, Lucas; da Silva Júnior, Delso Honório; Ferreira de Camargo, Fernanda Cristina; DeMoura, José Roberto; Trombetta, Ivani Credidio; de Almeida Correia, Marilia (ConScientiae Saúde, 2025)
Introduction: Policemen often face high stress and are prone to cardiovascular risks like hypertension, overweight, and dyslipidaemia. Identifying links between stress and early cardiovascular markers could help to detect those at risk. Objective: to compare autonomic function and sleep quality between policemen with stress and those without stress. Methods: Twenty-three policemen (39±7 years; 28.8±4.2 kg/m2) were divided into two groups: with and without stress, defined by Lipp's Stress Symptoms Inventory. Assessments involved sleep patterns (polysomnography) and autonomic function (blood pressure [BP], heart rate variability) during rest, and in response to physical (handgrip test), and mental (Stroop test) stressors. Mann-Whitney U test compared policemen with vs. without stress. Results: Policemen with stress exhibited higher sleep heart rate (63±9 bpm vs. 55±12 bpm, p=0.031), amount of snoring (530±225 vs. 158±247; p=0.003), and peak diastolic BP (116±20 mmHg vs. 95±21 mmHg; p=0.046) during handgrip compared to policemen without stress. Conclusion: Policemen with stress exhibit worse sleep quality and autonomic function than policemen without stress.